Validitas Media Pembelajaran Berbasis Mind Map pada Mata Pelajaran Dasar-Dasar Teknik Ketenagalistrikan di Sekolah Menengah Kejuruan - Hadi, Wice Nurul; Sardi, Juli (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This study discusses one of the stages of research on the development of learning media based on mind mapping for the learning basic subjects of electrical engineering namely validity testing. The validity of learning media based on mind mapping is divided into two aspects, namely media and material aspects. Each aspect is validated respectively by three validators who have expertise following these aspects (two lecturers from the Department of Electrical Engineering and one subject teacher). The instrument used in this validity test is a validity questionnaire that has gone through the instrument validation process before. The results showed that the learning media based on mind mapping for the learning basic subjects of electrical engineering developed was valid in all aspects of both media and material aspects. The media aspect obtained a value of 0,884 which means valid because more than 0,6, and the material aspect obtained a value of 0,854 which means valid because more than 0,6. Thus, it can be concluded that the learning media based on mind mapping for the learning basic subjects of electrical engineering is valid in both media and material aspects and suitable for use in the learning process.